Tafsir Otentik dan Tafsir Infiltratif: Studi Kritis dalam Metodologi Tafsir - Hozaini, M. Fahri; Sari, Mat (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
Al-Qur'an is the word of God which is the source of Islamic teachings in various dimensions of life, such as legal, social, worship, and so on. The verses of the Qur'an cannot always be understood or interpreted explicitly, sometimes the implied meaning is more substantive than the explicit meaning. To understand the meaning of the Qur'an implicitly requires special knowledge, namely the science of interpretation and other supporting prerequisite sciences. A meaning that is close to the truth can be obtained from the holy text of the Qur'an. Basically, the method of interpreting the Koran is divided into two, namely the interpretation of bi al-ma'tsur and the interpretation of bi al-ra'yi. Tafsir bi al-ma'tsur is a method of interpretation that is based on the Qur'an, as-Sunnah, the words of the Prophet’s companions and tabiin. Meanwhile, the interpretation of bi al-ra'yi is based on the scholar's ijtihad. Interpretation based on religious sources, which spirit and breath are based on the Qur'an, as-Sunnah, the words of the prophet’s companions or tabiin are referred to al-ashil (authentic interpretation). Meanwhile, al-dakhil (deviation interpretation) is a false interpretation because it does not contain interpretation elements outlined by salafussholeh or deviations in interpretation.